2017
DOI: 10.5603/kp.a2017.0017
|View full text |Cite
|
Sign up to set email alerts
|

Endogenic erythropoietin secretion in patients undergoing off-pump coronary artery bypass grafting

Abstract: A b s t r a c tBackground: Erythropoietin (EPO) deficiency or inadequate EPO secretion in response to bleeding may result in profound or prolonged anaemia after cardiac surgery. Aim:The aim of the study was to evaluate the changes in EPO secretion in patients undergoing off-pump coronary artery bypass grafting (OPCAB).Methods: Blood samples from 43 patients (mean age 65.1 ± 7.6 years) were obtained before surgery and on the 1 st , 2 nd , and 6 th day post isolated OPCAB. EPO levels ≥ 4.3 mIU/mL were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In Drohomirecka et al's study, it was conducted on 682 patients. 18% of the patients had a stenosis of more than 50% and 4.5% had a stenosis of more than 70% [11]. The prevalence of carotid artery stenosis of more than 50% in CABG patients has been from 2% to 18% in different studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In Drohomirecka et al's study, it was conducted on 682 patients. 18% of the patients had a stenosis of more than 50% and 4.5% had a stenosis of more than 70% [11]. The prevalence of carotid artery stenosis of more than 50% in CABG patients has been from 2% to 18% in different studies.…”
Section: Discussionmentioning
confidence: 97%
“…This means that more arterial stenosis was observed in patients with a history of CVA. In Drohomirecka et al's study, the history of CVA was considered one of the independent risk factors of stenosis [11]. The prevalence of previous CVA was 2.6% in Tarzamani et al's study [8].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the potential advantages of OPCABG is to attenuate systemic inflammatory responses caused by neutrophil activation [29]. Moreover, OPCABG is beneficial to the secretion of endogenous erythropoietin in patients, reducing the blood loss of surgery [30]. Studies have found that OPCABG is associated with decreased troponin I levels and activation, while elevated levels of troponin I and proinflammatory cytokines are present in most cardiac surgery patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of signif icant preoperative CAS may lead to postoperative neurological complications. [11] Previous studies have shown that MPV, NLR and PLR values, which can be easily obtained from routine blood parameters, can be used in the diagnosis and prognosis of cardiovascular diseases. Platelets play an important role in atherosclerotic cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%